1988
DOI: 10.1093/ajcp/89.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Rehydration of Air-Dried Smears with Normal Saline: Application in Fine-Needle Aspiration Cytologic Examination

Abstract: In fine-needle aspiration cytologic examination, nuclear features are often better assessed in hematoxylin and eosin (H and E) or Papanicolaou- (Pap) stained than Romanowsky-stained smears. However, both H and E and Pap stains require the use of immediately wet-fixed smears for cytomorphologic preservation. Some degree of air drying is usually inevitable. Placing air-dried smears in normal saline for 30 seconds before fixation in 95% alcohol is found to be a simple means of rehydrating the cells. The quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 5 publications
1
46
1
Order By: Relevance
“…Besides the disadvantages of cost and the non-availability of 95% ethyl alcohol at PHCs, delayed or prolonged fixation due to improper training of the staff in the peripheral setup leads to unsatisfactory staining and diagnostic difficulties, especially in developing countries where cervical cancer is very common [5]. Since the 1950s and 60s, there have been studies describing various methods of rehydration of ADS [7]. Among several reagents (normal saline, tap water and aqueous glycerine) which have been tried, normal saline is the simplest and cheapest fluid that is available to the laboratories and is considered the best offered rehydration fluid for ADS [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the disadvantages of cost and the non-availability of 95% ethyl alcohol at PHCs, delayed or prolonged fixation due to improper training of the staff in the peripheral setup leads to unsatisfactory staining and diagnostic difficulties, especially in developing countries where cervical cancer is very common [5]. Since the 1950s and 60s, there have been studies describing various methods of rehydration of ADS [7]. Among several reagents (normal saline, tap water and aqueous glycerine) which have been tried, normal saline is the simplest and cheapest fluid that is available to the laboratories and is considered the best offered rehydration fluid for ADS [3,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Rehydration of air-dried smears (ADS) has been suggested as a satisfactory alternative to wet fixation in fine-needle aspiration and effusion cytology. However, very few reports regarding the rehydration of cervical ADS as a substitute for WFS are available [6,7,8,9]. Studies using air-dried rehydrated techniques have shown results comparable to those of the wet-fixed technique without much differences between the percentage or degree of abnormalities ranging from inflammatory changes to frank malignancy [2,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…Some slides were rehydrated with saline for about five seconds, then immediately fixed with 95% acetic acid/alcohol and stained with a rapid Papanicolaou method, as previously described. 18,19 The remaining slides were stained with modified Romanowsky stain (Diff-Quik, Düdingen, Switzerland). The remaining specimen was rinsed and collected in CytoLyt TM (Cytyc Corp., Boxborough, Massachusetts, U.S.A.); then it was centrifuged in a Megafunnel TM (Thermo-Shandon, Pittsburgh, Pennsylvania, U.S.A.), transferred to a glass slide and stained with routine Papanicolaou stain.…”
Section: Methodsmentioning
confidence: 99%
“…The process of rehydration is essential for the RADPap stain [19]. In a previous study, several solutions were tested as rehydration solutions, and it was demonstrated that physiological saline was superior to the other solutions [2]. Following this report, many of the RAD-Pap protocols, including that of the present study, adopt physiological saline as the rehydration solution [6,18,22].…”
Section: Discussionmentioning
confidence: 76%
“…However, whether samples were stained successfully with RAD-Pap should be carefully evaluated, because it still requires a complicated multistep procedure. An erythrocyte-free background is an advantage of RAD-Pap in contrast to traditional Pap, and this phenomenon was considered due to hemolysis of red blood cells in the rehydration process [2,10]. However, the presence of erythrocytes is often useful for comparison of cell size [13,15].…”
Section: Discussionmentioning
confidence: 99%